Isoflurane conditioning improves functional outcomes after peripheral nerve injury in a sciatic cut repair murine model - Xu, Yameng; Yan, Ying; Zipfel, Gregory J.; MacEwan, Matthew; Ray, Wilson Z.; Athiraman, Umeshkumar (Frontiers in Neurology, 2024)
Introduction Anesthetic conditioning has been shown to provide neuroprotection in several neurological disorders. Whether anesthetic conditioning provides protection against peripheral nerve injuries remains unknown. The aim of our current study is to investigate the impact of isoflurane conditioning on the functional outcomes after peripheral nerve injury (PNI) in a rodent sciatic nerve injury model. Methods Adult male Lewis rats underwent sciatic nerve cut and repair and exposed to none (Group 1, sham), single isoflurane exposure (Group 2), three-time isoflurane exposure (Group 3), and six-time isoflurane exposure (Group 4). Isoflurane conditioning was established by administration of 2% isoflurane for 1 hour, beginning 1-hour post sciatic nerve cut and repair. Groups 3 and 4 were exposed to isoflurane for 1 hour, 3 and 6 consecutive days respectively. Functional outcomes assessed included compound muscle action potential (CMAP), evoked muscle force (tetanic and specific tetanic force), wet muscle mass, and axonal counting. Results We observed an increase in axons, myelin width and a decrease in G-ratio in the isoflurane conditioning groups (3- and 6-days). This correlated with a significant improvement in tetanic and specific tetanic forces, observed in both groups 3 and 4. Discussion Isoflurane conditioning (3- and 6-day groups) resulted in improvement in functional outcomes at 12 weeks post peripheral nerve injury and repair in a murine model. Future experiments should be focused on identifying the therapeutic window of isoflurane conditioning and exploring the underlying molecular mechanisms responsible for isoflurane conditioning induced neuroprotection in PNI.